The Syrian chaos. The conflict in Syria: consequences for Europe's security and defence - Cerqueira, J. (Proelium, 2016)
The Arab Spring has increased the chaos in the region by replacing the local and historical dictatorships with a political power vacuum. The struggle between Sunni and Shi’ite factions is being used as a tool of geo-strategic alignments and regional geopolitics, and also a clash within Muslim civilisation. Radical Islamic religious groups have taken advantage of the dispute to create a new political model, probably a new world order. A revolutionary reality, the Islamic State, takes its place in world politics. Europe is now threatened both by cross-border religious terrorism and massive flows of migrants at an extended period of economic stagnation. There is disagreement within the EU as jihadist attacks continue. Europe remains on maximum alert and in some cases in a state of emergency.